Delayed Replantation of an Avulsed Permanent Incisor Tooth - Wahluyo, Soegeng; Anggraini, Ratri; Anggarani, Welly; Ramadhaniati, Dwi Mulia; Tedjosasongko, Udijanto (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: Incidence of dental avulsion is 1-11% of all dental injuries to the permanent dentition, with the maxillary central incisor being the most frequently involved tooth. The age group of 7-10 years appears to be most affected. If the avulsed teeth are not treated immediately, they can have a significant negative impact on the child such as functional, aesthetic and psychological disorder. Purpose: The aims of this case reports was to discuss the important role of storage medium that can influence the success of replantation treatments of avulsion teeth. Case Management: The first phase of treatment was an extra oral root canal treatment and were repositioned into the socket. Clinical and radiographic control was carried out periodically for 2 months. Discussion: Delayed replantation has a poor long-term prognosis. The periodontal ligament will be necrotic and not expected to heal. The goal in delayed replantation is to restore the tooth to the dentition for esthetic, functional, and psychological reasons and to maintain alveolar contour. Conclusion: This case reports showed the important role of storage medium that can influence the success of replantation treatments of avulsion teeth.